1987
DOI: 10.1111/j.1348-0421.1987.tb03130.x
|View full text |Cite
|
Sign up to set email alerts
|

2‐Mercaptoethanol Acts as a Potentiating Factor of Interleukin‐2‐Dependent Lymphocyte Proliferation

Abstract: An interleukin-2 (IL-2) dependent cell line which could be grown continuously with crude concanavalin A-stimulated rat or mouse spleen cell culture supernatant could not survive for over 48 hr in the culture medium supplemented with partially purified or recombinant IL-2. The cell growth was restored by adding another factor obtained from the same crude culture supernatant. This potentiating activity which was physicochemically inseparable from serum albumin was also obtained from the culture medium containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Since many researchers have observed that BME promoted cell growth and differentiation such as murine B cells (Sugama et al 1987), human marrow osteoprogenitor cells (Inui et al 1997) and fetal neurons (Ni et al 2001), high concentrations of BME can also induce cell shrinkage and apoptosis (Lu et al 2004). Therefore, the optimal concentration of BME on the growth and osteogenic differentiation of hUMSCs in our study remains to be determined.…”
Section: Discussionmentioning
confidence: 88%
“…Since many researchers have observed that BME promoted cell growth and differentiation such as murine B cells (Sugama et al 1987), human marrow osteoprogenitor cells (Inui et al 1997) and fetal neurons (Ni et al 2001), high concentrations of BME can also induce cell shrinkage and apoptosis (Lu et al 2004). Therefore, the optimal concentration of BME on the growth and osteogenic differentiation of hUMSCs in our study remains to be determined.…”
Section: Discussionmentioning
confidence: 88%
“…These results indicate that the positive effects of adding 2-Mercaptoethanol in the cell culture media of MSCs vary depending on cell passage number and is needed more with increasing cell passage number. its positive impact on increasing the proliferation of lymphocytes [11,12]. The exact mechanisms of how 2-Mercaptoethanol increases the survival and proliferation rate of cells have not been clarified yet, and it is proposed to be logically related to its ability to expunge toxic products [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…2-Mercaptoethanol is a xenobiotic organosulfhydryl that has a powerful antioxidant ability to control the level of oxygen free radicals and prevent their toxic level [10][11][12]. The addition of 2-Mercaptoethanol to the cell culture medium was proposed 40 years ago to enhance the proliferation and survival of immune cells which is important to potentiate their immunological characteristics [11,12]. Nowadays, 2-Mercaptoethanol is routinely used in the cell culture media of many cell types whether they are adherent or suspended cells [8,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that 2-mercaptoethanol has a major impact on the behavior of cultured lymphocytes (18,19) because it promotes cystine transport and enhances lymphocyte survival and proliferation, possibly by increasing IL-2 production (19)(20)(21). In the present studies, viable cell numbers were not substantially increased by the use of 2-mercaptoethanol although the percentage of blast cells was increased and blast cell formation has been noted as a key part of a mitogen-induced response by T lymphocytes in which cytokine production occurs.…”
Section: Discussionmentioning
confidence: 99%